Damage resistant conductive iontophoresis electrode
Patent Information
- Application Number
- CN202211065255.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-01
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-09-01
AI Technical Summary
到目前为止,通过简便的节能方法制备具有所有这些复杂特性的生物安全I-skins仍然是一个巨大的挑战
[0013] (1) The conductive ion skin electrode of the present invention has excellent anti-fatigue, anti-damage sensing ability and regeneration ability;
Smart Images

Figure BDA0003828122110000081 
Figure HDA0003828122120000011 
Figure HDA0003828122120000012
Abstract
Description
Technical Field
[0001] This invention relates to the field of bionic skin technology, and in particular to a damage-resistant conductive ion skin electrode. Background Technology
[0002] Skin-like sensors have broad application prospects in wearable electronics, human-machine systems, implantable biomedical devices, and soft robotics. An ideal skin-like sensor possesses multiple functions, including stretchability, conductivity, adhesion, self-healing, mechanical strength, moldability, and recyclability; however, integrating these diverse functions requires extremely complex technologies. For example, ionic skin (I-skins) mimics natural skin to detect stimuli by converting electrical signals through ion conduction, typically requiring at least four steps. First, a stretchable hydrogel is generated using a polymer network, a step usually involving complex synthetic chemistry and energy-intensive heating-cooling operations. Second, to impart sufficient conductivity to the hydrogel, an inorganic salt or ionic liquid must be introduced through a lengthy ion exchange process or a cast film. Third, to fabricate the I-skin sensor, conductive gels are used to attach the conductive wires of the external circuitry to the ionic skin. Finally, additional adhesives are used to firmly adhere the ionic skin to the target substrate for the practical application.
[0003] The above steps not only increase costs and manufacturing time, but also pose risks of adhesion failure and ion leakage. Adhesion failure will lead to decreased sensing reliability, while ion leakage will trigger toxic reactions in biological systems.
[0004] Furthermore, integrating multiple properties of skin-like sensors often comes at the expense of certain specific properties. For example, sensors with enhanced mechanical strength typically have lower sensitivity, while sensors with sufficient ionic conductivity and stretchability are generally non-adhesive. To date, fabricating biosafety I-skins with all these complex properties using simple and energy-efficient methods remains a significant challenge. Summary of the Invention
[0005] To address the problems existing in the prior art, the present invention provides a damage-resistant conductive ion skin electrode.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a damage-resistant conductive ion skin electrode. When the conductive ion skin electrode is damaged, it can recover to the same current signal as when the conductive ion skin electrode is intact within a time delay, wherein the time delay does not exceed 2 seconds.
[0007] In a second aspect, the present invention provides a method for manufacturing a damage-resistant conductive ion skin electrode, comprising the following steps:
[0008] Step 1: Mix at least one cationic polyelectrolyte solution and at least one anionic polyelectrolyte solution to obtain a white precipitate;
[0009] Step 2: Press the white precipitate to obtain a conductive ion skin electrode;
[0010] Optionally, in step 3, the conductive ion skin electrode is left to stand or incubate until it becomes transparent.
[0011] Thirdly, the present invention provides the application of the damage-resistant conductive ion skin electrode obtained in the first or second aspect, preferably for wearable devices and skin sensors.
[0012] The beneficial effects of the anti-damage conductive ion skin electrode of the present invention include:
[0013] (1) The conductive ion skin electrode of the present invention has excellent anti-fatigue, anti-damage sensing ability and regeneration ability;
[0014] (2) The conductive ion skin electrode of the present invention can be perfectly adhered to the tissue without the use of additional adhesives, that is, the conductive ion skin electrode will always conform to the tissue, thereby enabling sensitive detection of three-dimensional (3D) physical strain.
[0015] (3) The conductive ion skin electrode of the present invention has skin-like mechanical strength and elasticity, ionic conductivity and recyclability. Attached Figure Description
[0016] Figure 1 In the image, A) and B) are SEM images of the white precipitate before and after pressing in Example 1, respectively; C) and D) are the corresponding images. Figure 1 A) and Figure 1 B) High-magnification SEM image; E) SEM image of the sample in Comparative Example 1;
[0017] Figure 2 A graph showing the conductivity data of conductive ion skin electrodes with different water contents;
[0018] Figure 3 In the figure, A) and B) are real-time current changes of the conductive ion skin electrode in Example 1 when it is cut by a knife of different lengths;
[0019] Figure 4 A schematic diagram showing the change in current when two fragments of conductive ion skin electrodes are in contact at different angles after being severed.
[0020] Figure 5 Figure 1 shows the simulation test results of salt bridges with different aspect ratios.
[0021] Figure 6In the text, A) represents the cell viability of BSC1 cells as determined by MTS in the presence of the conductive ion skin electrode of Example 1; B) represents the live / dead cell measurement data of BSC1 cells observed by CLSM in the presence or absence of the conductive ion skin electrode of Example 1.
[0022] Figure 7 In the diagram, A) represents the change of ΔR / R0 of the skin sensor with strain (ε); B) and C) represent the changes of ΔR / R0 of the skin sensor under different strains.
[0023] Figure 8 This is a schematic diagram of the signal from the sensor in Experiment 4 (left) and the non-adhesive (right) skin during the finger sensing test.
[0024] Figure 9 In the image, A) is a photograph of 3D finger bending detection using a skin sensor; B) is the 3D resistive response of finger bending.
[0025] Figure 10 In the following scenarios, A) monitoring a person's throat movements while saying "hello," "goodbye," and "Peking University"; B) monitoring the pulse signals before and after the activity.
[0026] Figure 11 In the image, A) shows a digital photograph taken using a commercial digitizer and an EMG signal measurement using the conductive ion skin electrode of Example 1; B) shows EMG signals acquired from a forearm with different gripping forces; and C) shows variations in EMG signal amplitude and force.
[0027] Figure 12 Figure 1 shows the EMG signal test results of different fingers before and after the self-repair and remodeling of the conductive ion skin electrode in Example 1, with different fingers flexion and extension.
[0028] Figure 13 The test results show that different signals were generated for different finger positions. Detailed Implementation
[0029] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby providing a clearer and more explicit definition of the scope of protection of the present invention.
[0030] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.
[0031] It is worth noting that the raw materials mentioned in this invention are known and can all be obtained commercially.
[0032] In a first aspect, the present invention provides a damage-resistant conductive ion skin electrode that, when damaged, can recover to the same current signal as when the conductive ion skin electrode is intact within a time delay, wherein the time delay does not exceed 2 seconds.
[0033] In this invention, when the conductive ion skin electrode is damaged by cuts or splits, its current can be restored to the original level (the current when the conductive ion skin electrode is undamaged) within 2 seconds, thus demonstrating that the conductive ion skin electrode has a high resistance to damage.
[0034] Research has shown that when a conductive iontophoresis electrode is cut with a tool, the current in the electrode immediately returns to its original level once the tool is removed from the electrode's surface. Alternatively, when a conductive iontophoresis electrode is broken into multiple fragments, the current when two fragments come into contact can return to their original level (i.e., the current of the intact electrode) within a time delay.
[0035] In this invention, the conductive ion skin electrode has a layered pore structure. The size and shape of the layered pores are similar to the morphology of the patches on the foot of a mussel, specifically, macropores of 3-5 μm form a polyelectrolyte network, while micropores of 100-200 nm exist on the walls between two adjacent macropores.
[0036] In this invention, the conductive ion skin electrode has mild adhesion and excellent fatigue resistance.
[0037] Studies have shown that this conductive ion skin electrode exhibits high adhesion to various substrates, such as copper, glass, wood, paper, rubber, dolomite, tetrafluoroethylene, and pigskin (which is biologically similar to human skin). It is particularly effective on pigskin, forming an interface with a toughness greater than 27.5 J / m. -2It exhibits effective adhesion with a shear strength exceeding 4.71 kPa, and after 5 peel-adhesion cycles, the interfacial toughness and shear strength show almost no change. This indicates that the adhesive strength of this conductive ion skin electrode does not fatigue and has excellent fatigue resistance.
[0038] It was also found that the adhesion strength increased with increasing adhesion time. In particular, the shear strength of copper increased significantly, reaching 35 kPa, while the increase in shear strength of pigskin was not obvious.
[0039] In this invention, the conductive ion skin electrode has high sensitivity.
[0040] Specifically, the conductive ion skin electrode can adhere to the tissue without the use of additional adhesives, meaning that the conductive ion skin electrode will always conform to the tissue, thereby enabling sensitive detection of three-dimensional (3D) physical strain, providing excellent sensitivity even for subtle differences in throat movements caused by different speech patterns.
[0041] Therefore, the wires of the external circuit can be bonded to the conductive ion skin electrode to create a skin sensor. This operation is simple and does not require additional conductive gel.
[0042] In a preferred embodiment of the present invention, the conductivity of the conductive ion skin electrode is 1 to 10 S / m.
[0043] Research has shown that the conductivity of this conductive ion skin electrode increases with increasing water content. The conductivity of the conductive ion skin electrode with a water content of 20% is 1 S / m, while the conductivity can reach 6 S / m when the water content is 70%.
[0044] In a preferred embodiment of the present invention, the stress of the conductive ion skin electrode is 20 kPa to 25 MPa.
[0045] Studies have shown that the mechanical strength of this conductive ion skin electrode decreases with increasing water content. When the water content of the conductive ion skin electrode is 20%, the stress can reach 8 MPa and the strain is 40%; when the water content of the conductive ion skin electrode is 55%, the stress can reach 70-80 kPa and the maximum strain exceeds 1300%.
[0046] In summary, in order to optimize various properties, preferably, the water content of the conductive ion skin electrode is between 10% and 80%, more preferably between 15% and 70%, and even more preferably between 20% and 55%.
[0047] Research has found that when conductive ion skin electrodes contain 55% water, they can achieve self-repair and, over time, can almost self-repair to their original level.
[0048] In this invention, the conductive ion skin electrode has a recycling capability.
[0049] When conductive ion skin electrode fragments are fully hydrated with water (soaked in water or water is added to the fragments to soften them), the conductive ion skin electrode fragments can be regenerated under mechanical pressure, and the mechanical strength of the regenerated conductive ion skin electrode is exactly the same as that of the original.
[0050] Research has shown that when two conductive ion skin electrode fragments come into close contact, the incision disappears within 60 minutes and can recover 94.6% of the tensile stress and 98.6% of the strain.
[0051] Preferably, the conductive ion skin electrode is prepared from at least one cationic polyelectrolyte and at least one anionic polyelectrolyte.
[0052] The cationic polyelectrolyte is a quaternary ammonium salt polyelectrolyte, which is preferably selected from at least one of polydimethyldiallyl ammonium chloride (PDDA), polypolymethacryloyloxyethyltrimethylammonium chloride, cationic polyacrylamide, chitosan quaternary ammonium salt, polyacrylamine hydrochloride, and polyethyleneimine, and more preferably polydimethyldiallyl ammonium chloride (PDDA).
[0053] The anionic polyelectrolyte is selected from at least one of polyacrylic acid, sodium alginate, sodium cellulose, anionic polyacrylamide, sodium polyglutamate, polylysine, and sodium polystyrene sulfonate. Preferably, the anionic polyelectrolyte is selected from sodium polyglutamate (SPG) and / or anionic polyacrylamide (APAm). All of the above anionic polyelectrolytes are biocompatible and non-toxic.
[0054] In current technology, the thin film materials of conductive ion skin electrodes mainly focus on two components, with only one major interaction (hydrogen bonding or electrostatic interaction) driving the formation of the film, which makes the performance of the film difficult to control.
[0055] Therefore, the key to this invention lies in how to prepare thin films with excellent properties in all aspects.
[0056] Extensive research has revealed that when fabricating conductive iontophoresis skin electrodes using one cationic polyelectrolyte and two anionic polyelectrolytes, where hydrogen bonds can form between the two anionic polyelectrolytes, the electrostatic interactions and hydrogen bonds of the three polyelectrolytes can be utilized to control the film's properties. In particular, when the cationic polyelectrolyte is polydiallyl ammonium chloride and the anionic polyelectrolytes are sodium polyglutamate and anionic polyacrylamide, the conductive iontophoresis skin electrodes prepared by using multi-component complexation to regulate non-covalent interactions exhibit excellent damage resistance.
[0057] Meanwhile, electrostatic interactions facilitate the self-repair process of the conductive ion skin electrode, but electrostatic interactions alone are insufficient. The precipitate composed of polydimethyldiallylammonium chloride and anionic polyacrylamide exhibits high elasticity but cannot self-repair. Conversely, the reduced resilience and increased hydrogen bonding between sodium polyglutamate and anionic polyacrylamide play a crucial role in self-repair. Therefore, the anionic polyelectrolyte of this invention is selected from sodium polyglutamate and anionic polyacrylamide.
[0058] Secondly, the present invention provides a method for preparing an anti-damage conductive ion skin electrode as described in the first aspect. This preparation method mainly includes the following steps:
[0059] Step 1: Mix at least one cationic polyelectrolyte solution and at least one anionic polyelectrolyte solution to obtain a white precipitate.
[0060] Preferably, the molar ratio of cationic polyelectrolyte to anionic polyelectrolyte is (0.5-1.5):1, more preferably (0.7-1.3):1, and even more preferably (0.9-1.1):1, for example 1:1.
[0061] The cationic polyelectrolyte is a quaternary ammonium salt polyelectrolyte, preferably selected from at least one of polydimethyldiallyl ammonium chloride (PDDA), polypolymethacryloyloxyethyltrimethylammonium chloride, cationic polyacrylamide, chitosan quaternary ammonium salt, polyacrylamine hydrochloride, and polyethyleneimine, and more preferably polydimethyldiallyl ammonium chloride (PDDA).
[0062] The anionic polyelectrolyte is selected from at least one of polyacrylic acid, sodium alginate, sodium cellulose, anionic polyacrylamide, sodium polyglutamate, polylysine and sodium polystyrene sulfonate, sodium polyglutamate and sodium polystyrene sulfonate, preferably, the anionic polyelectrolyte is selected from sodium polyglutamate (SPG) and / or anionic polyacrylamide (APAm).
[0063] The chemical formulas of PDDA, APAm, and SPG are shown below:
[0064]
[0065] Preferably, a cationic polyelectrolyte solution and two anionic polyelectrolyte solutions are mixed to obtain a white precipitate. More preferably, the cationic polyelectrolyte is PDDA, and the anionic polyelectrolytes are both APAm and SPG.
[0066] Extensive research has revealed that when only APAm is selected as the anionic polyelectrolyte, although the precipitate formed by PDDA and APAm exhibits good elasticity, it cannot form a conductive ionic skin electrode. When only SPG is selected as the anionic polyelectrolyte, PDDA and SPG can only form a viscous complex. However, when both APAm and SPG are selected as the anionic polyelectrolytes, and multi-component complexation is used to regulate non-covalent interactions, a conductive ionic skin electrode can be obtained. This conductive ionic skin electrode possesses skin-like mechanical strength and elasticity, ionic conductivity, self-healing properties, and recyclability.
[0067] Preferably, the molar ratio of APAm to SPG is (0.5-5):1, more preferably (1-4):1, for example 1:1 or 3:1.
[0068] Studies have shown that the elasticity and mechanical strength of conductive iontophoresis electrodes depend on the molar ratio of APAm and SPG. When the molar ratio of APAm to SPG is 3:1, the stress of the conductive iontophoresis electrode can reach as high as 8 MPa, and the strain exceeds 50%, exhibiting good mechanical strength. As the amount of SPG continues to increase, the mechanical strength of the conductive iontophoresis electrode decreases sharply, and the strain increases significantly. When the molar ratio of APAm to SPG is 1:1, the stress of the conductive iontophoresis electrode is approximately 2 MPa, and the strain exceeds 130%.
[0069] Applying conductive ion skin electrodes to wearable sensors requires further improvement in their mechanical strength. Research has found that the weight-average molecular weight of polydiallyl ammonium chloride (PDDA), sodium polyglutamate (SPG), and anionic polyacrylamide (APAm) significantly influences the performance of conductive ion skin electrodes. Specifically, the mechanical strength and toughness of the conductive ion skin electrode increase with increasing weight-average molecular weight, as does its hardness.
[0070] More preferably, the polydiallyl ammonium chloride (PDDA) has a weight-average molecular weight (Mw) of 200,000 to 800,000, preferably 400,000 to 500,000. Sodium polyglutamate (SPG) has a Mw of 40,000 to 200,000, preferably 50,000 to 150,000. Anionic polyacrylamide (APAm) has a Mw of 6 million to 15 million, preferably 8 million to 12 million. The conductive ion-modified skin electrode prepared using these three polyelectrolytes with average molecular weights within the aforementioned ranges exhibits the best mechanical properties.
[0071] More specifically, step 1 may include the following steps:
[0072] Step 1-1: Prepare a solution of polydimethyldiallylammonium chloride, a solution of sodium polyglutamate, and a solution of anionic polyacrylamide. Preferably, the solvent in all three solutions is water.
[0073] The concentration of the polydimethyldiallylammonium chloride solution is 1–200 mM; preferably 10–150 mM; more preferably 20–100 mM.
[0074] The concentration of the sodium polyglutamate solution is 1–200 mM; preferably 10–150 mM; more preferably 20–100 mM.
[0075] The concentration of the anionic polyacrylamide solution is 1–200 mM; preferably 10–150 mM; more preferably 20–100 mM.
[0076] In this invention, the total concentration of the above three solutions after mixing is 30-80 mM; preferably 40-70 mM, so as to generate a conductive ion skin electrode with better performance.
[0077] Steps 1-2: Mix the polydimethyldiallylammonium chloride solution, sodium polyglutamate solution, and anionic polyacrylamide solution to obtain a white precipitate.
[0078] In this invention, in order to quickly obtain a white precipitate, the mixed solution can be shaken, preferably by hand for 5 to 60 seconds, more preferably for 8 to 30 seconds, so that the mixed solution can immediately form a white precipitate.
[0079] Step 2: Press the white precipitate to obtain a conductive ion skin electrode.
[0080] Preferably, the white precipitate is pressed under a mechanical pressure of 0.1 to 1 MPa to obtain a white conductive ion skin electrode.
[0081] The mechanical stress refers to the pressure applied to the white precipitate that is greater than 0 and less than 1000 MPa. This pressure can be the sample's own weight or external stress; external stress can be centrifugal force, rolling pressure, finger pressure, press pressure, pasta machine pressure, etc., and can be applied by various parts of the human body or assisted by various mechanical devices. The pressure required for pressure-induced conversion may vary for conductive ion skin electrodes prepared from different raw materials.
[0082] Preferably, the white precipitate is pressed into a conductive ion skin electrode with a thickness of 0.3 to 3 mm, more preferably 1 mm.
[0083] The white precipitate contains approximately 3% sodium chloride, which is a counterion captured during the precipitation process.
[0084] Optionally, in step 3, the conductive ion skin electrode is left to stand or incubate until it becomes transparent.
[0085] The purpose of this step is to enable the formation of hydrogen bonds and electrostatic interactions between the cationic polyelectrolyte and the anionic polyelectrolyte.
[0086] Preferably, the conductive ion skin electrode is dried in a dry environment (such as a desiccator) for 1 to 4 hours, preferably 2 to 3 hours, for example 2.5 hours, or incubated in an oven at 60°C for 0.2 to 1.5 hours, preferably 0.3 to 1 hour, for example 0.5 hours, until the white conductive ion skin electrode becomes transparent.
[0087] Unbound by theory, the mechanism of this process may involve APAm and SPG exhibiting fibrous and network structures in water, respectively, while PDDA forms spherical particles with an average particle size of approximately 44 nm. When the three are mixed, electrostatic interactions occur between PDDA and APAm / SPG, and hydrogen bonds form between APAm and SPG, immediately forming a "putty-like" precipitate. Under relatively low mechanical pressure, the precipitate can transform into a soft, white film. The white appearance indicates large phase boundaries between the polyelectrolytes within the film. During the pressing process, the electrostatic interactions and hydrogen bonds between the polyelectrolytes remain unchanged. However, after a period of resting or incubation, the polyelectrolyte chains rearrange, resulting in a transparent conductive ion-exchange skin electrode.
[0088] In this invention, a solid-phase molecular self-assembly (SPMSA) strategy is used to balance the electrostatics and hydrogen bonds of three polyelectrolytes—PDDA, APAm, and SPG—to fabricate a self-adhesive, stretchable, flexible, self-healing, remodelable, ultra-durable, and extremely sensitive damage-inert conductive ion skin electrode. This conductive ion skin electrode can capture small ions and possesses continuous water channels, ensuring unimpeded ion transport even under damage, allowing the fabricated skin sensor to maintain ultra-high real-time sensitivity even when damaged.
[0089] Thirdly, the present invention provides the application of the damage-resistant conductive ion skin electrode obtained in the first or second aspect, preferably for wearable devices and skin sensors.
[0090] To further understand the present invention, the conductive ion skin electrode provided by the present invention is described below with reference to embodiments. The scope of protection of the present invention is not limited by the following embodiments.
[0091] Example
[0092] Example 1
[0093] A 100 mM solution of anionic polyacrylamide (APAm, weight average molecular weight Mw = 12,000,000), a 100 mM solution of sodium polyglutamate (SPG, Mw = 50,000–150,000), and a 100 mM solution of polydimethyldiallylammonium chloride (PDDA, Mw = 400,000–500,000) were mixed, and water was added to make the total concentration of the mixed solution 50 mM.
[0094] A white precipitate was obtained after shaking the mixed solution by hand for 10 seconds.
[0095] Place the white precipitate between two moistened polytetrafluoroethylene plates and apply a mechanical pressure of 1 MPa for 5 seconds.
[0096] The white precipitate was incubated in a 60°C oven for 0.5 hours to obtain a transparent conductive ion skin electrode.
[0097] Example 2
[0098] The preparation process is similar to that of Example 1, except that the conductive ion skin electrode of Example 1 is placed in a vacuum drying oven and dried for 3 hours to obtain a dried conductive ion skin electrode.
[0099] The dried conductive ion skin electrode was placed in a sealed container for 6 hours. The sealed container contained anhydrous calcium chloride, resulting in a conductive ion skin electrode with a water content of 5%.
[0100] Example 3
[0101] The preparation process is similar to that in Example 2, except that the dried conductive ion skin electrode is placed in a sealed container for 8 hours. The sealed container contains a sub-container filled with a saturated sodium chloride solution, resulting in a conductive ion skin electrode with a water content of 25%.
[0102] Example 4
[0103] The preparation process is similar to that in Example 2, except that the dried conductive ion skin electrode is placed in a sealed container for 16 hours. The sealed container contains a sub-container filled with a saturated sodium chloride solution, resulting in a conductive ion skin electrode with a water content of 35%.
[0104] Example 5
[0105] The preparation process is similar to that in Example 2, except that the dried conductive ion skin electrode is placed in a sealed container for 12 hours, and a sub-container containing an aqueous solution is placed inside the sealed container to obtain a conductive ion skin electrode with a water content of 55%.
[0106] Example 6
[0107] The preparation process is similar to that in Example 2, except that the dried conductive ion skin electrode is placed in a sealed container filled with water for 24 hours to obtain a conductive ion skin electrode with a water content of 70%.
[0108] Comparative Example
[0109] Comparative Example 1
[0110] The preparation process is similar to that in Example 1, except that sodium polyglutamate solution is not added.
[0111] Comparative Example 2
[0112] The preparation process is similar to that in Example 1, except that no anionic polyacrylamide solution is added.
[0113] Experimental Example
[0114] Experiment Example 1: TEM Test
[0115] Scanning electron microscopy (SEM) measurements were performed using a Hitachi S4800 microscope at an accelerating voltage of 1.0 kV.
[0116] Figure 1 A) and Figure 1 B) SEM images of the white precipitate before and after pressing in Example 1, respectively; Figure 1 C) and Figure 1 D) are respectively the corresponding Figure 1 A) and Figure 1 B) High-magnification SEM image; Figure 1 E) is the SEM image of the sample in Comparative Example 1.
[0117] from Figure 1 As can be seen, there are large phase boundaries between the polyelectrolytes aggregated in the white precipitate. Furthermore, the electrostatic interactions and hydrogen bonds between the polyelectrolytes remained unchanged before and after pressing.
[0118] Meanwhile, the white precipitate exhibits stratified pores, the formation of which may be driven by osmotic pressure. Macropores of 3–5 μm form a polyelectrolyte network, while micropores of 100–200 nm exist on the walls between adjacent macropores. The presence of micropores may be closely related to the hydrogen bonding of SPG.
[0119] and Figure 1 In contrast, no pores are generated when SPG is absent, indicating that the hydrogen bonds between SPG and APAm can generate a denser network.
[0120] Experiment Example 2: Ionic Conductivity Test
[0121] The voltage on the conductive ion skin electrode is controlled to a constant 1.0V, and the current change is monitored during movement and speaking. The resistance change (ΔR / R0) can then be calculated based on the change in current, where ΔR = |R - R0|, and R0 and R are the original resistance and the resistance under applied strain ε, respectively.
[0122] The dried conductive iontophoresis skin electrode contains 3.4% NaCl, which provides the conditions for its conductivity. Figure 2 The conductivity of conductive ion-conducting skin electrodes with different water contents. From Figure 2 As can be seen, the conductivity of the conductive ion skin electrode with a water content of 20% (Example 1) is 1 S / m. The conductivity gradually increases with increasing water content. For the conductive ion skin electrode with a water content of 55%, the conductivity reaches as high as 5.7 S / m.
[0123] Figure 3 In the figure, A) and B) are real-time current changes of the conductive ion skin electrode in Example 1 when it is cut by a knife of different lengths.
[0124] Figure 3 A) It can be seen that the current recovers immediately when the blade leaves the cutting line. Furthermore, for cutting lines of 1 to 4 cm, the recovered current does not change after the blade is immediately removed. Figure 3 B) It can be seen that when the conductive ion skin electrode is cut in half, the current decreases steadily with a low amplitude, and the current recovers immediately after the two fragments of the conductive ion skin electrode come into contact, with almost no time delay.
[0125] Figure 4 This diagram illustrates the change in current when two fragments of conductive ion skin electrodes are in contact at different angles after being severed.
[0126] Figure 4 It can be seen that when two conductive ion skin electrode fragments are in parallel or perpendicular contact, the current remains basically unchanged, even though the contact area of perpendicular contact is only 1 / 10 of the damaged area. This demonstrates that the conductive ion skin electrode has excellent damage resistance and conductivity.
[0127] Figure 5 The figure shows the simulation test results of salt bridges with different aspect ratios.
[0128] Figure 5 It can be seen that the current intensity is proportional to the width of the salt bridge, but when the salt bridge width is the same as the overall width, the current cannot return to its original level. This indicates that the hierarchical porosity in the conductive ion skin electrode is crucial for the extremely fast propagation of the electric field, making it possible for the current conductive ion skin electrode to be used as a damage-resistant strain sensor.
[0129] Experimental Example 3: Cytotoxicity MTS Assay and Live / Dead Fluorescence Imaging
[0130] Monkey kidney epithelial cells (BSC1) were cultured in Invitrogen α-MEM containing 5% fetal bovine serum (FBS) (Thermo-Fischer Scientific, USA), with the addition of 1% sodium pyruvate (Gibco), 1% gluta MAX™-1 (Gibco), and 1% penicillin-streptomycin (Thermo-Fischer Scientific, USA). BSC1 cells were then incubated at 37°C in a 5% CO2 incubator.
[0131] Add 1.5 mL of BSC1 cell suspension (approximately 5 x 10⁻⁶ cells) 3 BSC1 cells were seeded into 24-well plates (purchased from Costa Corning Corp.) and cultured for 1 day. Then, 1.5 mL of α-MEM containing BSC1 cells was exposed to 5 mm gel discs (30–40 mg) for 1, 2, and 3 days. The conductive ion skin electrode of Example 1, dispersed in α-MEM, was indirectly delivered to adherent cells. Cytotoxicity was determined by 40 μL MTS (2 mg / mL). As a positive control, BSC1 cells began to grow in α-MEM. After incubation at 37°C for 1 hour, absorbance was measured at 490 nm using a microplate reader (Synergy H1, Bio-Tek) to calculate cell viability.
[0132] In addition, after indirect contact with the conductive ion skin electrode of Example 1, a live / dead cell staining assay was performed to qualitatively assess and visualize cell viability.
[0133] BSC1 cells (density 5*10) 4 BSC1 cells were seeded at 1 / L into glass dishes (35 mm in diameter, 10 mm well, purchased from Cellvis) and grown in α-MEM for 1 day. Subsequently, the conductive ion skin electrode of Example 1 was indirectly exposed for 1, 2, and 3 days in culture dishes containing 2 mL of α-MEM containing BSC1 cells. Cells were stained using a live / dead assay. Live cells stained green with calcein AM, while dead cells stained red with ethidium bromide dimer 1. For the positive control, BSC1 cells were incubated with pure α-MEM before adding live / dead cells. Fluorescence images were obtained using a confocal laser scanning microscope (LSM 900 with Airyscan). Specific test results are as follows: Figure 6 As shown.
[0134] Figure 6A) indicates that the cell viability of BSC1 cells was measured by MTS in the presence of the conductive ion skin electrode in Example 1; Figure 6 B) Data on the live / dead cell count of BSC1 cells observed by CLSM with or without the conductive ion skin electrode of Example 1 (scale bar 50 μm).
[0135] from Figure 6 As shown in A), in the presence of the conductive ion skin electrode of Example 1, the cell viability of BSC1 cells was 93±3%, 92±3%, and 91±3% at 1, 2, and 3 days, respectively, indicating that the conductive ion skin electrode has very low cytotoxicity. Figure 6 As shown in B), the conductive ion skin electrode had no effect on cell viability.
[0136] Experiment Example 4: Sensor Performance Testing
[0137] A skin sensor is fabricated by pressing the copper strip of the external circuit onto the conductive ion skin electrode in Example 1.
[0138] (1) Skin sensor ΔR / R0 as a function of strain (ε) test.
[0139] Figure 7 A) is the change of ΔR / R0 of the skin sensor as a function of strain (ε); Figure 7 B) and 7C) represent the changes in ΔR / R0 of the skin sensor under different strains.
[0140] Figure 7 A) It can be seen that the ΔR / R0 signal has a significant response to each mechanical strain. Furthermore, ΔR / R0 exhibits a high response at low strain levels (0–50%). Figure 7 B)) and 50-200% high strain ( Figure 7 The slopes under C)) are 1.59 and 2.85, respectively, which indicates that the skin sensor has high sensitivity and reliability over a large sensing range, and therefore can be used as a wearable strain sensor.
[0141] (2) Testing of skin sensors in 3D sensing.
[0142] The skin sensor in this experimental example has adhesive properties. Figure 8 This is a schematic diagram of the signals from the skin sensor in this experimental example (left) and the non-adhesive (right) skin sensor during a finger bending test.
[0143] from Figure 8 As can be seen, compared with non-adhesive skin sensors, the skin sensor in this experimental example can provide a smoother signal and lower noise, thus enabling the skin sensor to record any body movement in 3D.
[0144] Figure 9To use skin sensors for 3D sensing of body movement.
[0145] Figure 9 A) A photograph showing 3D finger bending detection using a skin sensor; Figure 9 B) is the 3D resistive response of finger bending.
[0146] like Figure 9 As shown in A), the copper strips of three external circuits are directly pressed onto a rectangular skin sensor along two perpendicular directions and one diagonal direction. The highest signal strength (ΔR / R0 approximately 18%) is observed along the parallel direction, while the lowest signal strength (ΔR / R0 approximately 8%) is observed along the perpendicular direction. Figure 9 B). The signal along the diagonal lies between the parallel and perpendicular signals, indicating that the skin deformation of the bent finger is mainly along the parallel direction.
[0147] Figure 10 A) To monitor a person's throat movements, say "hello," "goodbye," and "Peking University" respectively; Figure 10 B) is a signal used to monitor a person's pulse before and after activity.
[0148] Using the above results, the human throat movements produced by different sounds can be reflected by different signals. Figure 10 A)) This demonstrates that spoken information can be accurately interpreted without hearing the sound. Furthermore, readable laryngeal movements make it possible to "hear" the speech of deaf-mute individuals. It can even be detected that after movement, the pulse's ΔR / R0 signal significantly increases ( Figure 10 B)) Therefore, conductive ion skin electrodes can monitor signal changes before and after body movement in real time.
[0149] Experiment Example 5: Electromyography (EMG) Signal Testing
[0150] A conductive ion skin electrode of Example 1 with a diameter of 2.0 cm was placed parallel to the inner layer of skin on the left forearm, and another conductive ion skin electrode was attached to the elbow as a ground electrode. Figure 11 A)).
[0151] The conductive ion skin electrode detected an EMG signal with a signal-to-noise ratio (SNR) of 44.5 dB, which is more than 60% higher than the 27.8 dB of a conventional electrode. Furthermore, the EMG signal is proportional to the force detected. Figure 11 B) and 11C)), therefore, conductive ion skin electrodes can be used for human-computer interaction to monitor various precise human movements.
[0152] Figure 12 The image shows the EMG signal test results of different fingers before and after the self-repair and remodeling of the conductive ion skin electrode in Example 1.
[0153] Figure 12 This indicates that the conductive ion skin electrode can stably provide ultra-high sensitivity real-time EMG signals even with cutting lines. Regardless of whether the conductive ion skin electrode was cut into two or four parts, the EMG signals of different fingers did not change significantly, thus demonstrating that the conductive ion skin electrode is a damage-inert skin-like electrode.
[0154] Figure 13 A) It shows that different gestures of the five fingers can generate different signals, and these signals can be remotely and in real time identified by the robotic hand's fingers, thus enabling the robotic hand to produce identical movements. Figure 13 B)).
[0155] The present invention has been described in detail above with reference to specific embodiments and exemplary examples. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the present invention, and all such modifications and improvements fall within the scope of the present invention.
Claims
1. A damage-resistant conductive ion skin electrode, characterized in that, When the conductive ion skin electrode is damaged, it can recover to the same current signal as when the conductive ion skin electrode is intact within a time delay, wherein the time delay does not exceed 2 seconds; This damage-resistant conductive ion skin electrode is prepared by the following method: Step 1: Mix anionic polyacrylamide solution with a weight average molecular weight Mw of 12,000,000, sodium polyglutamate solution with a weight average molecular weight Mw of 50,000~150,000, and polydimethyldiallyl ammonium chloride solution with a weight average molecular weight Mw of 400,000~500,000. After shaking the mixed solution by hand for 10 seconds, a white precipitate is obtained. Step 2: Press the white precipitate to obtain the conductive ion skin electrode; Step 3: Let the conductive ion skin electrode stand or incubate until the conductive ion skin electrode becomes transparent.
2. The anti-damage conductive ion skin electrode according to claim 1, characterized in that, The conductivity of the conductive ion skin electrode is 1~10 S / m.
3. The anti-damage conductive ion skin electrode according to claim 1 or 2, characterized in that, The water content of the conductive ion skin electrode is between 10% and 80%.
4. A method for preparing an anti-damage conductive ion skin electrode as described in claim 1, characterized in that, Includes the following steps: Step 1: Mix anionic polyacrylamide solution, sodium polyglutamate solution, and polydimethyldiallyl ammonium chloride solution. Shake the mixed solution by hand for 10 seconds to obtain a white precipitate. Step 2: Press the white precipitate to obtain the conductive ion skin electrode; Step 3: Let the conductive ion skin electrode stand or incubate until the conductive ion skin electrode becomes transparent.
5. The preparation method according to claim 4, characterized in that, Step 1 includes: Step 1-1: Prepare polydimethyldiallylammonium chloride solution, sodium polyglutamate solution, and anionic polyacrylamide solution; Steps 1-2: Mix the polydimethyldiallylammonium chloride solution, sodium polyglutamate solution, and anionic polyacrylamide solution to obtain a white precipitate.
6. The preparation method according to claim 5, characterized in that, In step 1-1, the molar ratio of anionic polyacrylamide to sodium polyglutamate is (0.5~5):
1.
7. The application of the damage-resistant conductive ion skin electrode according to any one of claims 1-3 or the damage-resistant conductive ion skin electrode obtained by any one of claims 4-6, for use in wearable devices and skin sensors.